Adaptaciones curriculares y su influencia en la educación inclusiva en estudiantes de la UE Réplica Eugenio Espejo, Babahoyo. 2022 - Castro Morán, Leydi Johanna (2023)
Inclusive education is conceived as an important event for educational quality and for it to be carried out, the application of curricular adaptations is essential as a mechanism to respond to the educational needs of students. Although it is true that this very transcendental topic has been discussed for a long time and one of the significant advances is access to regular education, but inclusion goes beyond simply letting in, but rather involves involving all students of the construction of knowledge, for this reason the present investigation aims to determine that the relationship that exists between curricular adaptations and inclusive education is very significant since they are linked to each other. In this way, the study was carried out in the Eugenio Espejo Replica Educational Unit in Babahoyo, taking as a sample 19 students with Special Educational Needs who were surveyed and as support for the investigation, the person in charge of the Student Counseling Department was interviewed. This process was developed under a mixed approach and with a descriptive, explanatory and inductive-deductive design, in order to describe the phenomenon, find the cause-effect relationship and obtain specific conclusions. Thus, the need to train teachers in the use of didactic strategies that provide adequate attention to students who present educational needs was evidenced, in addition, it was objected how essential management is in the application of guidelines and policies that regulate The education.